Localization of a mosquito-larval toxin of Bacillus sphaericus 1593. - Myers, P S (1980)
Cell-free wall, membrane, and cytoplasmic fractions were prepared from Bacillus sphaericus 1593, which exhibited toxic activity against larvae of the mosquito Culex pipiens var. quinquefasciatus. Breakage of 12- to 14-h cells by sonication or French pressure cell yielded toxic material which could be assayed in a standard mosquito larva bioassay. When sporulating cells of strain 1593 were fractionated, the majority of the toxic activity was localized in the cell wall rather than in the plasma membrane or cytoplasm. The toxin located in the bacterial cell wall was relatively stable, in that activity was unaffected by treatment with trypsin, pronase, CHCl3-CH3OH-water, Triton X-100, 8 M urea (30 min), heat (80 degrees C, 12 min), sonication, refrigeration, lyophilization, or freezing. Activity was destroyed by boiling for 10 min or by 0.01 N NaOH. Only about 1.0% of the activity present in purified cell walls could be recovered by a 2-h extraction with 8 M urea or 3 M guanidine hydrochloride. A comparison of the toxicity of a cell-free cell wall fraction with that of a sample consisting entirely of heat-stable spores indicated that the spore preparation was about 10 times more active.